Oocyte yield of nulliparous and pluriparous buf- faloes submitted to synchronization prior to fol- licular aspiration - Claudio Coutinho Bartolomeu; Mayumi Santos Botelho Ono; André Mariano Batista; Paulo Castelo Branco de Gouveia Filho; Lucas Carvalho Perreira; Raquel Desenzi Pessoa; Rafael Artur da Silva Junior (Revista Científica)
This study aimed to analyze the quantity and quality of oocytes obtained from buffaloes submitted to follicular aspiration (OPU) after synchronization of the follicular wave emergency. So, 10 nulliparous and 10 pluriparous buffaloes were submitted to follicular aspirations. The data showed no differences in the number of oocytes obtained when the aspirations were done on days 4 or 5 after the follicular wave emergency. Although, when considering the buffaloes category, nulliparous buffaloes presented a higher mean number of retrieved oocytes/OPU (25.00 ± 3.36 vs. 13.40±1.14), viable oocytes/OPU (6.22 ± 1.62 vs. 3.60 ± 1.27) and a total of recovered oocytes (250 vs. 134). On the other hand, considering the day of aspirations, there was no difference when OPU was done on day four or day 5. According to the results, it can be concluded that nulliparous buffaloes yield twice as many oocytes as pluriparous buffaloes, making them a good choice of category to be used to improve embryo production by IVF in the species.